Dual-readout calorimetry, an integrated high-resolution solution for energy measurements at future electron-positron colliders - Antonello, Maddalena; Caccia, M.; Ferrari, R.; Franchino, Silvia; Gaudio, G.; Hauptman, J.; Lee, S.; Pezzotti, L.; Salvatore, F.; Santoro, R.; Vivarelli, I.; Wigmans, R. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2020)
Future circular electron-positron colliders operating at s=90, 160, 240 and 350 GeV as Z, W, H and t factories will demand experiments with superior momentum and energy resolution for all the possible final-state particles produced. The IDEA Detector aims at satisfying these requests by exploiting an ultra-light drift chamber as the largest central tracker and a dual-readout fiber calorimeter for both electromagnetic and hadronic energy measurements. In this paper I review the dual-readout calorimeter baseline choices, as well as the related R&D work.
Available online 7 April 2019
Gesehen am 06.04.2020